Protein phosphorylation regulation of key genes in oral squamous cell carcinoma and their role in the immune microenvironment - Zeng, Yu; Wang, Chunyang; Zhao, Wenli; Zhao, Ye (Frontiers in Immunology, 2025)
BackgroundOral squamous cell carcinoma (OSCC) is one of the most common malignant tumors in the head and neck region, with a complex molecular mechanism that has not yet been fully elucidated. This study aims to identify key genes closely associated with the development and progression of OSCC through integrative multi-omics data analysis and to explore the potential roles of these genes in protein phosphorylation regulation and the immune microenvironment, providing new insights for precision diagnosis and treatment.MethodsThe study integrated data from National Center for Biotechnology Information (NCBI) and National Institutes of Health (NIH) sources, combining differential expression gene analysis and co-expression network construction to identify candidate genes significantly associated with phosphorylation status. Key genes were further screened, and molecular subtyping of samples was performed based on gene expression patterns. Additionally, the association between key genes and immune microenvironment characteristics was evaluated, and Mendelian randomization (MR) was employed to investigate the impact of genetic variants on disease risk.ResultsThe analysis revealed multiple significantly differentially expressed genes, primarily enriched in pathways related to cell cycle regulation, signal transduction, and metabolism. Five key genes—BMP2, FN1, INHBA, MMP9, and THY1—were ultimately identified. These genes exhibited subtype-specific expression patterns across different molecular subtypes and were closely associated with immune cell infiltration levels. Furthermore, functional validation demonstrated that FN1 was significantly linked to OSCC occurrence at the genetic level.ConclusionThis study identified key genes and molecular subtypes associated with OSCC, highlighting their potential links to protein phosphorylation and the immune microenvironment. Among these, FN1 may serve as a potential risk gene and a candidate biomarker, providing novel insights into the molecular mechanisms of OSCC.